Comparing Mental Health of School-Age Children with and without Epilepsy - SHAMSAEI, Farshid; CHERAGHI, Fatemeh; ZAMANI, Gholamreza (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Shamsaei F, Cheraghi F, Zamani Ghr. Comparing Mental Health of School-Age Children with and without Epilepsy: A Case Control Study. Iran J Child Neurol. Summer 2016; 10(3):35-41. Abstract Objective Mental health problems frequently occur in children with epilepsy but the diagnosis is frequently missed and therapeutic opportunities are often lost. The aim of this study was to compare mental health statues between school-aged children with epilepsy and the healthy group. Materials & Methods In this case, control study, 120 children aged 6 to 12 years with idiopathic epilepsy and 240 healthy control groups were followed up. Children with epilepsy were enrolled from Iranian Epilepsy Association in 2014. The parent version of Child Symptom Inventory-4 questionnaire was used. Mean comparisons were performed using Student’s t test while effect sizes were estimated by Cohen’s d coefficient. The Chi-Square test was used to assess the difference between frequency distribution of demographic variables in both groups. The significance level was considered less than 0.05. Results There were statistically significant differences between children with epilepsy and control group as for attention deficit hyperactivity disorder, generalized anxiety disorder, major depression, separation anxiety, social phobia, motor and vocal tics and oppositional defiant disorder. Conclusion The carefully evaluating and prospectively following the psychopathology symptom of children with epilepsy are critical for early identification, prevention and treatment. References Valizadeh L, Barzegar M, Akbarbegloo M, Zamanzadeh V, Rahiminia E, Ferguson CF. The relationship between psychosocial care and attitudes toward illness in adolescents with epilepsy. Epilepsy Behav 2013; 27(1):267-71. Russ SA, Larson K, Halfon N. A national profile of childhood epilepsy and seizure disorder. Pediatrics 2002; 129(2):256-264. Kotsopoulos IA, van Merode T, Kessels FG, de Krom MC, Knottnerus, JA. Systematic review and meta-analysis of incidence studies of epilepsy and unprovoked seizures. Epilepsia 2002; 43(11):402–1409. Sayehmiri K, Tavan H, Sayehmiri F, Mohamadi I, Carson KV. Prevalence of Epilepsy in Iran: A Meta-Analysis and Systematic Review. Iran J Child Neurol 2014; 8(4): 9–17. Salpekar JA, Dunn DW. Psychiatric and psychosocial consequences of pediatric epilepsy. Semin Pediatr Neurol 2007; 14(4): 181-8. Ott D, Siddarth P, Gurbani S, Koh S, Tournay A, Shields WD, Caplan R. Behavioral disorders in pediatric epilepsy: unmet psychiatric need. Epilepsia 2003; 44(4): 591-597. Davies S, Heyman I, Goodman R. A population survey of mental health problems in children with epilepsy. Dev Med Child Neurol 2003; 45(5):292-295. Maia Filho HS, Costa CRM, Gomes MM. Epilepsia e Saúde Mental na Infância. J Epilep Clin Neurophysiol 2006; 12(2):79-88. Gaitatzis A, Carroll K, Majeed A, Sander J. The epidemiology of the comorbidity of epilepsy in the general population. Epilepsia 2004; 45(2):1613-1622. Jones JE, Watson R, Sheth R, Caplan R, Koehn M, Seidenberg M, Hermann B. Psychiatric comorbidity in children with new onset epilepsy. Dev Med Child Neurol 2007; 49(7):493-7. Gadow KD, Sprafkin J. Child symptom inventory-4 Screening and norms manual. Stony Brook, NY: checkmate Plus Ltd, 2002. Dulcan MK, Mina K. Dulcan’s Textbook of Child and Adolescent Psychiatry. 1st ed, American Psychiatric Pub, 2010. Jafari N, Mohammadi MR, Khanbani M, Farid S, Chiti P. Effect of Play Therapy on Behavioral Problems of Maladjusted Preschool Children. Iran J Psychiatry 2011 6(1): 37–42. Hermann B, Jones J, Dabbs K, Allen CA, Sheth R, Fine J, McMillan A, Seidenberg M. The frequency, complications and etiology of ADHD in new onset pediatric epilepsy. Brain 2007; 130(Pt 12):3135-48. Kaner AM. Psychiatric Comorbidity in Children with Epilepsy … or Is It: Epilepsy Comorbidity in Children with Psychiatric Disorders? Epilepsy Curr 2008; 8(1): 10–12. Williams J Steel C, Sharp GB, DelosReyes E, Phillips T, Bates S, Lange B, Griebel ML. Parental anxiety and quality of life in children with epilepsy. Epilepsy Behav 2003; 4(5): 483–486. Stefanello S, Marín-Léon L, Fernandes PT, Li LM, Botega NJ. Depression and anxiety in a community sample with epilepsy in Brazil. Arq Neuropsiquiatria 2011; 69 (2):342-348. Dunn DW, Austin JK, Perkins SM. Prevalence of psychopathology in childhood epilepsy: categorical and dimensional measures. Dev Med Child Neurol 2009; 51(5):364-372. McDermott S, Mani S, Krishnaswami S. A population-based analysis of specific behavior problems associated with childhood seizures. J Epilepsy 1995; 8(2):110–118. Davies S, HeymanI Goodman R. Apopulation survey of mental health problems in children with epilepsy. Dev Med Child Neurol 2003; 45(5):292-295. Parisi R, Moavero R, Verrotti A, Curatolo P. Attention deficit hyperactivity disorder in children with epilepsy. Brain Dev 2010; 32(1):10–16.